The Effect of Numbered Heads Together (NHT) Model Assisted with Audio Visual Media On The Learning Outcomes of Identifying Story Elements of Students Grade V - Prayekti, Hesty; Haryadi, Haryadi; Utomo, Udi (Journal of Primary Education, 2019)
Education is the spearhead of the progress of a nation. One factor in the formation of quality education must be balanced with quality of learning so that it has an effect on good student learning outcomes. The purpose of this research was to find out the benefit of numbered heads together (NHT) model assisted with audio visual media on the material of story elements in improving student learning outcomes of grade V. Data collection techniques was done by using learning outcomes test. The processing of the moderator variable test was done by using SPSS statistics 25 with moderated regression analysis technique with the first analysis by using the F test and the second analysis by using the R square value. The results showed that (1) the NHT model and audio visual media simultaneously influenced the student learning outcomes as evidenced in the F test of 0.000 < of the probability of 0.05; (2) the NHT model affects student learning outcomes by 38.9%, while the remaining 61.1% is influenced by other variables outside this regression; (3) The NHT model with audio visual media affects student learning outcomes by 58.4%, whereas, the remaining 41.6% is influenced by other variables outside this regression.